2023
DOI: 10.1021/acsnano.3c04984
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Ultrathin Carbon Layer on Porous Hard Carbon Boosts Sodium Storage with High Initial Coulombic Efficiency

Dejian Cheng,
Zhenghui Li,
Minglu Zhang
et al.

Abstract: Hard carbon (HC) has been widely adopted as the anode material for sodium ion batteries (NIBs). However, it is troubled by a low initial Coulombic efficiency (ICE) due to its porous structure. Herein, a graphitized and ultrathin carbon layer coating on HC is proposed to solve this challenge. The as-prepared porous carbon material coated with an ultrathin carbon layer composite (PCS@V@C) exhibits a cavity structure, which is prepared by using bis(cyclopentadienyl) nickel (CP−Ni) as the carbon source for outer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The excellent rate capability and cycling stability of XA-4T-1300 can be attributed to the effective regulation of AC by the pitch. In this study, we compare the specific capacity and ICE of XA-4T-1300 with those of recently reported anode materials for SIBs (Figure f). ,, The optimized sample XA-4T-1300 in this study exhibits a favorable ICE and specific capacity.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The excellent rate capability and cycling stability of XA-4T-1300 can be attributed to the effective regulation of AC by the pitch. In this study, we compare the specific capacity and ICE of XA-4T-1300 with those of recently reported anode materials for SIBs (Figure f). ,, The optimized sample XA-4T-1300 in this study exhibits a favorable ICE and specific capacity.…”
Section: Resultsmentioning
confidence: 84%
“…For XA-4T-1300, the capacity retention is 64.9% after 50 cycles at 100 mA g –1 (Figure c). Despite the extensive research dedicated to developing anode materials for SIBs (Table S6), ,,, this work still has its advantages. These results all indicate that the composite materials prepared in this study have broad prospects for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…When b approaches 1, charge storage in the cell is mainly controlled by capacitive behavior. When b nears 0.5, it is principally governed by semilinear diffusion processes . The b value was calculated from the linear plot of log( i ) versus log( v ), yielding values of 0.79 for the cathode and 0.7 for the anode.…”
Section: Results and Discussionmentioning
confidence: 99%
“…4c), corresponding to 47.6% of ICE. The ICE is relatively low due to the formation of the solid electrolyte interface (SEI) layer and the occurrence of irreversible side reactions [51]. Except for the irreversible discharge loss in the rst cycle, the GCD curves show slope characteristics without obvious plateau, indicating good electrochemical kinetic behavior of the material [52].…”
Section: The Electrochemical Performance Of Wdpc As For Anode Materia...mentioning
confidence: 99%